FRI0131 Rheumatoid arthritis patients with higher disease severity and subclinical carotid plaque experience more cardiovascular events despite a favorable conventional cadiovascular risk profile. (23rd January 2014) - Hong, S.J.; Kim, S.M.; Song, R.; Hur, J.-W.; Lee, S.H.; Yang, H.I.; Lee, Y.A.
Abstract : Background: It has been shown that patients with rheumatoid arthritis (RA) experience cardiovascular (CV) events more often than expected. Increased risk of CV disease in RA patients cannot be fully explained by conventional CV risk factors. This raises the possibility that the systemic inflammatory burden in RA may bring about its high CV event rate by causing accelerated atherosclerosis Objectives: This study was designed to evaluate the extent of subclinical atherosclerosis by measuring intima-media thickness of the carotid arteries (C-IMT) and the presence of plaque among RA patients and controls and to determine whether subclinical atherosclerosis such as increased C-IMT or plaque presence, RA associated features, and other conventional CV risk factors are associated with later development of CV disease in RA patients Methods: C-IMT was measured in 126 RA patients and 85 OA patients as controls who had no experience of CV events. The C-IMT was evaluated at common carotid arteries (CCAs), carotid bifurcation (BF) and internal carotid arteries (ICAs), bilaterally. Mean and maximal (max) IMTs were calculated from three measurements at each site. The following data were obtained for every patient: age, sex, body mass index (BMI), presence of bone erosions, rheumatoid factor, anti-CCP, medications, hypertension, hypercholesterolemia, diabetes mellitus, smoking status, family history of CV diseases, ESR and CRP levels. Thereafter, these patients have been followed-up and examined the CV event rate during seven years. The CVD was defined as myocardial infarction, unstable angina, cardiac arrest, or death due to ischemic heart disease. Results: Unlike expectations, mean and max C-IMT did not show the difference between RA and OA patients. But, we found the higher presence of carotid plaque in RA patients than in OA patients. During follow-up, 21patients experienced CV events. The incidence of CV events was higher in RA than OA (15.0% vs. 3.5%, p=0.004). But, the conventional CV risk factors such as DM, hypertension and high BMI were fewer in RA than in OA (10.3%, 27.7%, 34.1% vs. 28.2%, 55.2%, 57.6%, p=0.000). More CV events occurred in RA patients who initially showed the presence of subclinical plaque and the duration of CV event-free survival was shorter in RA patients with carotid plaque than those without (10 vs. 31months, p=0.051). The RA patients who developed CVD later had more bony erosion, higher positivity for rheumatoid factor or anti-CCP, high dose of steroid and higher levels of ESR and CRP, than those who did not. Conclusions: Despite a favorable conventional CV risk profile, our RA patients had significantly increased incidence rate of CVD than OA patients. RA itself was an independent risk factor for CVD. Especially, RA patients with carotid plaque, seropositivity, bony erosion, higher ESR and CRP, and high dose of used glucocorticoids are at higher risk of CVD. Disclosure of Interest: None Declared